Large-scale candidate gene study to identify genetic risk factors predictive of paliperidone treatment response in patients with schizophrenia. Issue 4 (April 2015) - Wang, Dai; Fu, Dong-Jing; Wu, Xiaodong; Shapiro, Alice; Favis, Reyna; Savitz, Adam; Chung, Hedy; Alphs, Larry; Gopal, Srihari; Haas, Magali; Cohen, Nadine; Li, Qingqin
<x xml:space="preserve">Abstract</x> Objective Clinical response to antipsychotic medications can vary markedly in patients with schizophrenia. Identifying genetic variants associated with treatment response could help optimize patient care and outcome. To this end, we carried out a large-scale candidate gene study to identify genetic risk factors predictive of paliperidone efficacy. Patients and methods A central nervous system custom chip containing single nucleotide polymorphisms from 1204 candidate genes was utilized to genotype a discovery cohort of 684 schizophrenia patients from four clinical studies of paliperidone extended-release and paliperidone palmitate. Variants predictive of paliperidone efficacy were identified and further tested in four independent replication cohorts of schizophrenic patients (N=2856). Results We identified an SNP in ERBB4 that may contribute toward differential treatment response to paliperidone. The association trended in the same direction as the discovery cohort in two of the four replication cohorts, but ultimately did not survive multiple testing corrections. The association was not replicated in the other two independent cohorts. We also report several SNPs in well-known schizophrenia candidate genes that show suggestive associations with paliperidone efficacy. Conclusion These preliminary findings suggest that genetic variation in the ERBB4 gene may differentially affect treatment response to paliperidone in individuals with schizophrenia. They implicate the neuregulin 1 (NRG1)–ErbB4 pathway for modulating antipsychotic response. However, these findings were not robustly reproduced in replication cohorts.